On the management and digestion of interactivity in the context of digital TV (RuMoRes, 2010)
This article intends to analyze the possibilities, conflicts and challenges related to the interactivity on digital TV. To achieve this purpose implies to reflect about the place of digital TV in a discursive strategies space that dialogue with the discursive gender TV and with the multimedia convergence, whose most evident example is the internet.